The prevalence of malocclusion and orthodontic treatment need in Omani adolescent population - Laila Al Jadidi; Sharanya Sabrish; Prashantha Govinakovi Shivamurthy; Viswapurna Senguttuvan (Wolters Kluwer Medknow Publications, 2018)
OBJECTIVE: To determine the prevalence of malocclusion and orthodontic treatment need in a sample of Omani adolescents aged 11-16 years. MATERIALS AND METHODS: The total sample included 854 adolescents with 387 boys and 467 girls between the age of 11 and 16 years with no previous orthodontic treatment history. The study design was cross-sectional. The parameters studied were skeletal relationship, lip competency, teeth impactions, missing teeth, contact point displacement, crowding, spacing, incisors and molars classification, overjet, overbite, crossbite, oral hygiene and caries. The Index of Orthodontic Treatment Need (IOTN) was used to study the need for orthodontic treatment for the total sample. RESULTS: There was a high prevalence of Class I jaw relationship (86.2%). About 81.6% of the sample studied had Class I molar relationship and 73.8% had Class I incisors relationship. About 61.4% of the sample had no contact displacement, while 5.2% had contact displacement >4 mm. Severe crowding in the maxilla was found in 2.3% while spacing was found in 24.2%. Around 11% of the sample studied had Class II div 1 incisors relationship, 13.5% Class III and only 1.8% had Class II div 2 incisors relationship. Only 8.6% of the sample studied had an overjet >6 mm while 16.3% had a deep bite and 0.2% had anterior open bite of >4 mm. Teeth impaction was found in 11.7% while permanent missing teeth was present in 1.8%. The results showed that 13.9% had a very great need for treatment while 43.2% of the sample did not need any treatment. CONCLUSION: Among the Omani adolescents, there was a high prevalence of Class I jaw relations and Class I molar relationship. The prevalence of malocclusion and treatment need in Omanis shows some variation when compared to other ethnicities.